THE ROLE OF MENTAL MINDFULNESS IN PROMOTING CONTRIBUTIONS OF ORGANIZATIONAL BRILLIANCE-APPLIED STUDY ON ADMINISTRATIVE LEADERS IN GOVERNMENT BANKS/ BABYLON - Jwan Fadel Mahdi (Scholars Digest Publishing, 2025)
The current research aimed to study mental alertness with its factors (awareness of responsibility, awareness discriminate, awareness of new openness, awareness of flexibility of behavior), as in independent variables and impact on achieving enhanced contribution to organizational brilliance, The research sought to achieve a goal represented by testing the relationship between the variables and the impact of one on the other, and it emerged from it, Several main and sub- hypotheses, and government banks were chosen collectively to research and test their hypotheses, The research sample consisted of (60) individuals in the researched organization, In order to verify the validity of the hypotheses that were built, as well as to process the data relied upon for the answers of the research sample, The use of the statistical program (SPSS) was used, and appropriate statistical methods, were chosen that Are consistent with the nature of the research, The results showed, The study indicates that there is a correlation and significant effect between mental alertness at the aggregate level of the responding sample by enhancing its contribution to organizational brilliance, A set of conclusions were reached based on the results of the study, and finally the research presented a number of proposals.
Keywords: Mental mindfulness and promoting the contribution of organizational brilliance.